Forensic Potential of MMPs and CC Chemokines for Wound Age Determination. Issue 6 (3rd August 2015) - Wang, Yenan; Yamamoto, Yuki; Kuninaka, Yumi; Kondo, Toshikazu; Furukawa, Fukumi
Abstract: In this study, we investigated time‐dependent expression of matrix metalloproteases (MMP)‐2, MMP‐9, chemokine CC motif ligand (CCL)‐2, CCL‐3, CCL‐5, IL‐1β, IL‐6, and TNF‐α mRNA at the skin injury site and sought their forensic potentials during the skin wound repair process. The tested wound ages in 42 mouse skin wounds were distributed at 0d, 1d, 3d, 5d, 7d, 10d, and 14d, respectively and then followed by real‐time polymerase chain reaction. Ultimately, MMP‐2 played an important role in the inflammation phase. On the contrary, MMP‐9 became involved at a later phase during wound healing. Meanwhile, CCL‐2 and CCL‐3 were active throughout almost all of the process. However, CCL‐5 mRNA had no significance. Collectively, an MMP‐9/MMP‐2 ratio of over 0.84 indicated that skin wound healing age was strongly 5 days or less. So elevated gene expressions of cytokines and chemokines in different phases of wound ages implied that combined exploration could make wound age determination more accurate and objective.